STRENGTHENING STUDENTS’ DISCIPLINE CHARACTER THROUGH THE “5 TEPAT” PRACTICE IN ELEMENTARY SCHOOL - Suyitno; Ana Andriani; Subuh Anggoro; Wakhudin (SOSIOEDUKASI, 2026)
The low level of student discipline, as reflected in a lack of punctuality, adherence to rules, understanding of the importance of discipline, and attitudes that do not yet align with norms of politeness, forms the background of this study. The purpose of this research is to describe the implementation of the “5 Tepat” (on time, in the right place, on the right task, following the right rules, and with the right attitude) habituation in strengthening students’ disciplinary character in elementary schools, to identify implementation challenges, and to analyze supporting and inhibiting factors.This study employs a descriptive qualitative approach with a case study design at SD Negeri Cisuru 05, Cilacap Regency. The research subjects include the principal, teachers, and students selected purposively. Data collection techniques consist of observation, interviews, and documentation. Data validity is ensured through source and technique triangulation, as well as member checking to enhance credibility. Data analysis follows the interactive model of Miles, Huberman, and Saldaña, involving data condensation, data display, and conclusion drawing.The results indicate that the “5 Tepat” habituation is implemented systematically through stages of understanding, routine practice, and evaluation and reflection. Most aspects of discipline have developed well, particularly being in the right place, following the right rules, and demonstrating the right attitude. However, punctuality and task completion still require reinforcement, as they have not been consistently achieved by all students. Implementation challenges include differences in student characteristics, low internal awareness, limited supervision, and the influence of the family environment. The success of the program is supported by school policies, teacher role modeling, collaboration among teachers, and parental involvement. The “5 Tepat” habituation has the potential to become an effective model for strengthening disciplinary character if implemented consistently and sustainably.